Effect of edaphic silicon on the quality and postharvest of ‘Dorado’ peach (Prunus persica) fruits - Álvarez-Herrera, Javier Giovanni; Molano-Diaz, Julian Mauricio; Camacho-Torres, Yenny Maritza (Revista de Ciencias Agrícolas, 2023)
In recent years, Colombia has seen an increase in the demand for peach fruits, but despite having adequate areas for peach production, neither production nor quality has increased because these fruits have a short post-harvest life and low firmness, which makes them susceptible to manipulation. The nutritional element Silicon affects the quality of these fruits when applied in fertilization, increasing firmness values, improving color, and favoring the concentration of metabolites. Therefore, the objective was to evaluate the edaphic application of different doses of silicon in the postharvest behavior of 'Dorado' peach fruits to maintain quality during storage for a longer time. A completely randomized block design with two blocks (stratum 1 and stratum 2) and five treatments (0, 300, 600, 900, or 120 kg ha-1 of silicon) was evaluated. The fruits from plants fertilized with 1200 kg ha-1 of Si showed more firmness and total soluble solids (TSS); however, the application of Si did not affect the other parameters. Fruits from stratum 1 had higher firmness and TSS than those from stratum 2, while the total carotenoids were not affected by stratum. The total titratable acidity and luminosity of the fruits decreased during postharvest, while the TSS only showed a slight increase. The respiratory rate presented the highest value ​​at 11 days of storage.